Nation, Face, and Identity: An Initial Investigation of National Face in East Asia - Chen, Rong; Hwang, Kwang-Kuo (Frontiers in Psychology, 2016)
This research investigates a key concept in East Asia, face, and represents the first attempt to empirically examine the concept of face at the national level. Controlling for the level of national identification, Study 1 employed the scenario experiment method among nationally representative samples of native Chinese and Taiwanese populations and revealed that national face exhibits patterns reverse of personal face. Using the experimental method, Study 2 replicated the findings of Study 1 and provided support for the different mechanisms underneath national face and personal face. Study 3 replicated the findings of Study 2 and additionally showed that national face exerts a significant inhibitory effect on face process. Findings are discussed in terms of possible implications for intergroup and international relations. Expanding on extant scholarship on face and across three studies with different experimental paradigms, this research turns our attention from face at the personal level to face at the national level by introducing the construct of national face and examining its manifestations in East Asia. The results advance our understanding of the psychological mechanism driving face concern in East Asia. They make a strong and unique case for the psychological existence of national face as an empirically distinct construct and an important psychological resource for East Asians.